Stress, Depression and Anxiety Levels Among Parents of Children with Neurodevelopmental Disorders Neurodevelopmental Disorders (Journal of Asian Development Studies, 2025)
In Pakistan, parents of children with neurodevelopmental disorders (NDDs) often face substantial psychological strain due to limited mental health resources, social stigma, and culturally embedded caregiving responsibilities. The present study examined levels of stress, depression, and anxiety among parents of children with NDDs and explored the relationships among these variables within the Pakistani context. Using a cross-sectional correlational design, data were collected through purposive sampling from 200 parents (100 mothers and 100 fathers) recruited from special needs institutions across Pakistan. Participants completed a demographic information sheet and the Depression Anxiety Stress Scale–21 (DASS-21). Data were analyzed using SPSS version 27. The findings revealed elevated levels of stress, depression, and anxiety among parents. Correlational analyses demonstrated significant positive relationships among stress, depression, and anxiety, with depression showing strong associations with both stress and anxiety. Independent samples t-tests further indicated significant gender differences, with mothers reporting significantly higher levels of depression, anxiety, and stress than fathers. These findings underscore the heightened psychological burden experienced by parents—particularly mothers— caring for children with neurodevelopmental disorders in Pakistan. The results highlight the urgent need for routine psychological screening, gender-sensitive psychosocial interventions, and culturally appropriate caregiver support services to address parental mental health within Pakistan’s resource-constrained healthcare system.